Stress ribbon and cable-supported pedestrian bridges - Strasky, Jiri (Thomas Telford, 2005)
Looks at how slender concrete deck are used in the design of suspension and cable stayed structures. This title describes structural types, addresses general design criteria, technology static and dynamic analysis, and discusses the results of the static and dynamic loading tests.
Keywords: Footbridges -- Design and construction.; Cable-stayed bridges -- Design and construction.; Suspension bridges -- Design and construction.; elektronické knihy; electronic books